IBM Storage Fusion Backup and Restore for IBM Cloud Pak for Data - Acevedo, Paulina; Stewart, Austen; Tosseth, Todd (IBM Redbooks, 2023)
IBM Cloud Pak® for Data can be protected with IBM Spectrum Fusion™. This IBM Redpaper publication covers backing up IBM Cloud Pak for Data with a non-disruptive (online) backup and then restoring to an alternate cluster. During an online backup, normal runtime operations in the Cloud Pak for Data cluster continue while the backup completes. The backup process includes creating policies and automating backups in IBM Spectrum Fusion, then protecting Cloud Pak for Data, protecting IBM Spectrum Fusion namespace and the IBM Spectrum® Protect Plus (SPP) catalog. Backup and restore is supported from IBM Storage Fusion HCI to IBM Spectrum Fusion software as well as from IBM Storage Fusion Software to IBM Storage Fusion HCI.